Impact of Biogenic Amines on the Growth of a Chlorella vulgaris Culture - Oleskin, Alexander V.; Postnov, Andrey L.; Boyang, Cao (Journal of Pharmacy and Nutrition Sciences, 2021)
The present work aims to develop a new approach enabling biotechnologists to increase the yield of Chlorella vulgaris biomass by means of biogenic amines (serotonin, dopamine, and histamine) that are known to stimulate growth of various unicellular organisms. C. vulgaris strain ALP was cultivated in the light with constant aeration at 24oC in a minerals-containing medium. Experimental systems contained 1, 10, or 100 mM of dopamine, histamine, or serotonin. Algal cells were counted using a light microscope. Serotonin caused a slight increase in biomass yield at a concentration of 10 mM, but not at the other tested concentrations. 1 and 10 mM (but not 100 mM) dopamine increased the cell number in the C. vulgaris culture at early cultivation stages. Histamine is the most efficient growth stimulator at concentrations of 1 and 10 mM, but not at a concentration of 100 mM, which even proved inhibitory to the algal culture. The data obtained demonstrate that the neurochemicals exert a stimulatory influence on the growth of the Chlorella culture at relatively low (micromolar) concentrations. Since animals often produce biogenic amines in response to stress or injury, the data give grounds for the suggestion that planktonic algae can benefit, in terms of growth rate, from the substances released by stressed or wounded representatives of aquatic fauna. In biotechnological terms, the data obtained hold some promise with regard to developing a relatively economical technique of boosting Chlorella biomass production.